2017
DOI: 10.1038/s41598-017-01269-3
|View full text |Cite
|
Sign up to set email alerts
|

Repeated inoculation of cattle rumen with bison rumen contents alters the rumen microbiome and improves nitrogen digestibility in cattle

Abstract: Future growth in demand for meat and milk, and the socioeconomic and environmental challenges that farmers face, represent a “grand challenge for humanity”. Improving the digestibility of crop residues such as straw could enhance the sustainability of ruminant production systems. Here, we investigated if transfer of rumen contents from bison to cattle could alter the rumen microbiome and enhance total tract digestibility of a barley straw-based diet. Beef heifers were adapted to the diet for 28 days prior to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
65
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(71 citation statements)
references
References 82 publications
5
65
1
Order By: Relevance
“…Both of these studies included a total mixed ration (TMR) containing significant levels of concentrate so it would be interesting to examine whether this relationship holds in cattle fed a diet with high forage and little to no concentrate. We recently conducted a study with cattle fed a 70% barley straw diet and observed apparent neutral detergent fibre digestibility ranging from 42.2% to 61.1% (Ribeiro et al, 2017). Fibre digestibility in this study was highly correlated with Metadinium protozoa.…”
Section: Studying the Rumen Microbiome With -Omics Approachesmentioning
confidence: 62%
See 2 more Smart Citations
“…Both of these studies included a total mixed ration (TMR) containing significant levels of concentrate so it would be interesting to examine whether this relationship holds in cattle fed a diet with high forage and little to no concentrate. We recently conducted a study with cattle fed a 70% barley straw diet and observed apparent neutral detergent fibre digestibility ranging from 42.2% to 61.1% (Ribeiro et al, 2017). Fibre digestibility in this study was highly correlated with Metadinium protozoa.…”
Section: Studying the Rumen Microbiome With -Omics Approachesmentioning
confidence: 62%
“…The observed increase in Fibrobacteriaceae was suggested to be due to an increased level of lignocellulose in the diet from the addition of straw (3% of diet DM) to the diet. This hypothesis is supported by Ribeiro et al (2017) who found that Fibrobacteraceae accounted for 25% of the OTUs in rumen solids from heifers fed a 70% barley straw diet. In other studies, Fibrobacteriaceae were only a minor component in cattle fed TMR diets indicating that variability between animals likely exists (Callaway et al, 2010;Zened et al, 2013).…”
Section: Impact Of Forage On the Rumen Microbiomementioning
confidence: 62%
See 1 more Smart Citation
“…The rationale behind much of this interest is due to the knowledge that variation in feed efficiency between breeds or genetic lines of food producing animals likely has a gut microbial component, where certain livestock have gut microbes capable of harvesting energy from the diet at higher rates. Ribeiro et al (2017) investigated the interspecies transfer of bison rumen microbes to beef cattle in an effort to improve feed efficiency. The authors hypothesized that rumen microbes from bison may be more adapted to fiber digestion in low quality feedstuffs.…”
Section: Fmt Use In Livestockmentioning
confidence: 99%
“…The authors hypothesized that rumen microbes from bison may be more adapted to fiber digestion in low quality feedstuffs. After removal of 70% of the endogenous rumen microbes in the recipient cattle, two transfaunates from bison resulted in increased nitrogen digestion and feed intake of the cattle, but did not affect fiber digestion of a barley straw diet (Ribeiro et al, 2017). In another study with poultry, FMT from highly feed-efficient donors was administered in the first several days of a chicken's life in an effort to enhance feed efficiency over subsequent weeks.…”
Section: Fmt Use In Livestockmentioning
confidence: 99%